Chocolate and corn flour : history, race, and place in the making of "Black" Mexico - Lewis, Laura A., 1959- (Online access with subscription: Duke University Press., 2012)
Chocolate and Corn Flour explores the history and contemporary culture of African descended Mexicans in the agricultural village of San Nicolás on the southern Pacific Coast of Guerrero (the Costa Chica). This ethnography emphasizes that local history is crucial to understanding identity and explores how racial categories are complicated by globalization and the influence of outsiders.